2021
DOI: 10.29053/2413-7138/2019/v7a3
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting Discourses on Conceptualising Children With Disabilities in Africa

Abstract: Despite the wide ratification of the United Nations Convention on the Rights of Persons with Disabilities, children with disabilities are still marginalised and their status as rights holders not fully acknowledged in many parts of Africa. In response to the call for research to focus on a distinct African conceptualisation of disability , an exploratory desk study was conducted on the disability discourse on children with disabilities in Africa. Though the authors uncovered positive African cultural and legis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For example, people with albinism are referred to as "nkau" (which stands for monkey) in Eswatini, and "meffu" in Cameron (which stands for the dead). It portrays that people with a disability are despised in African society; hence, fewer services are afforded to them by their communities (Tesemma and Coetzee 2019). Such a negative attitude toward people with disabilities in society affects the schools' attitude toward learners with disabilities, resulting in teachers not accommodating these learners.…”
Section: Society's Attitude Toward Disabilitiesmentioning
confidence: 99%
“…For example, people with albinism are referred to as "nkau" (which stands for monkey) in Eswatini, and "meffu" in Cameron (which stands for the dead). It portrays that people with a disability are despised in African society; hence, fewer services are afforded to them by their communities (Tesemma and Coetzee 2019). Such a negative attitude toward people with disabilities in society affects the schools' attitude toward learners with disabilities, resulting in teachers not accommodating these learners.…”
Section: Society's Attitude Toward Disabilitiesmentioning
confidence: 99%
“…Studies have shown that quality inclusive education promotes social integration, reduces prejudice and equips learners for positive contribution to communities (Aboud et al, 2012;Juvonen et al, 2019;Maulsharif et al, 2022). Despite being the subject of a longstanding global conversation, learners with disabilities continue to get the least opportunities and benefits from education, particularly in sub-Saharan Africa, where pre-schooling for children with disabilities aged 0 to 6 years is not common (Tesemma, 2011). Vulnerabilities such as poverty, malnutrition, disability, discrimination and poor education hinder optimal development (Aboud & Yousafzai, 2016;Black et al, 2017;Engel et al, 2007;McCoy et al, 2016;UNICEF, 2013UNICEF, , 2019UNICEF, , 2020.…”
mentioning
confidence: 99%